The Kirk and the Union. Issue 1 (February 2018) - Gay, Doug
Abstract : The Church of Scotland remained neutral in the 2014 independence referendum and its set piece dialogue on the referendum at the 2014 General Assembly made little impact. As one of the keynote speakers in the dialogue, Doug Gay discusses the declining influence of the Kirk in Scottish public life, arguing that its social and political role has been reduced but should not be discounted.